Comparative Analysis between Controlled Release Paroxetine and Extended-Release Venlafaxine for Treatment of Depression (Journal of Nobel Medical College, 2022)
Backgroud: Depression is a common condition seen in Psychiatry outpatient department. The treatment data suggest that the drugs that modulate the serotonergic neurotransmission are effective in the treatment of depression. Serotonin and nor Epinephrine re uptake inhibitors are also being used to treat depression. This study is aimed at comparing the results of a selective serotonin re-Uptake inhibitor (Paroxetine) to that of both Serotonin and Nor-Adrenaline re-Uptake inhibitor (Venlafaxine). Comparative analysis between the effects of Controlled release Paroxetine and extended-release Venlafaxine for treatment of depression in eastern Nepal.Materials and Methods: It is a prospective, open and randomized comparison. One Hundred consecutive patients who attended the Psychiatry outpatient door of Nobel Medical College and Teaching Hospital and diagnosed as Depression were enrolled for this study after being divided into 2 groups: Group 1 also being named as Paroxetine group while Group 2 as Venelafaxine group. The 100 patients were enrolled after being followed all the required protocols including Montgomery Asberg rating Scale readings and data were recorded on Day 0, Week 1, 2,3,4,6,8.Results: According to the analysis of the Montgomery Asberg rating Scale scores at baseline and after completion of study at 8weeks, both Paroxetine Controlled Release and Venlafaxine Extended-release treated patients improved similarly. But, many of the Venlafaxine-treated patients had nausea and constipation (p